Os conectivos e a relação de sentidos no texto: uma proposta para o ensino de língua por meio do uso do coordenador “mas”. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
It is a recurring fact in the education system, the great difficulty that students in the final years of elementary school, have in recognizing problems of textual coherence and organization of paragraphs in written productions. Among the causes of these difficulties are those related to the use of connectives, as they do not always know how to establish the meanings that these language mechanisms can attribute to the text. In search of finding alternatives that can contribute to a language teaching practice that can expand the student's linguistic knowledge, in order to equip him to better develop written productions, the following problematizing question arose: How to develop in 9th grade students of elementary school II of a state school in the municipality of Parintins-Am the ability to identify problems of cohesion and coherence in their own texts? Seeking to resolve this issue, we established the general objective of this research to investigate how activities using the connective “mas” can enable the student to recognize problems of cohesion and coherence in the text itself. The theoretical basis of this work refers to Franchi (2006), Cunha and Cintra (2017), Neves (2011,2017,2018, 2021), Koch (2018) Vieira (2017, 2019) among others. The methodology used was developed from the diagnostic analysis of data that were collected through the production of a dissertation-argumentative text, in which it was verified how students use the coordinating textual connectives and specifically analyzed which meanings the coordinator “mas” presents in the teachers’ texts, based on the polysemy of this connective presented by Cunha and Cintra (2017), Neves (2011). It is considered in this study that the diagnostic analysis is a fundamental part of the work with the teaching of grammar, because it is from the uses that the teacher will be able to verify how a linguistic element behaves in the communicative sphere of the student. For this, a didactic sequence was elaborated based on Vieira's proposal (2017) as a suggestion for language teaching anchored in linguistic studies and, in this way, to contribute with Portuguese language teachers to the development of the reflective study of grammar.
Keywords: Ensino de língua; Conectivos; Produção Textual; CNPQ:: Lingüística, Letras e Artes